Impact of early dolomitization on multi-scale petrophysical heterogeneities and fracture intensity of low-porosity platform carbonates (Albian-Cenomanian, southern Apennines, Italy). (May 2016) - Giorgioni, M.; Iannace, A.; D'Amore, M.; Dati, F.; Galluccio, L.; Guerriero, V.; Mazzoli, S.; Parente, M.; Strauss, C.; Vitale, S.
Abstract: Petrographic, petrophysical and fracture analyses were carried out on middle Cretaceous platform carbonates of the southern Apennines (Italy) that represent an outcrop analogue of the Val d'Agri and Tempa Rossa reservoirs of the Basilicata region. The studied outcrops, which are made of interlayered limestones and dolomites of inner platform environment, were selected to study the impact of dolomitization on reservoir properties and the control of dolomite texture on fracture development. Two types of dolomites – both formed during very early diagenesis – were found interlayered, at a metre scale, with micrite-rich limestones (mainly mudstones and wackestones). Dolomite A is fine-to medium crystalline and makes non-planar mosaics. Dolomite B is coarse-crystalline and makes planar-s and planar-e mosaics. The intercrystalline space of the planar-e subtype of dolomite B is either open or filled by un-replaced micrite or by late calcite or saddle dolomite cement. Dolomite A and dolomite B have similar average porosities of 3.7 and 3.1% respectively, which are significantly higher than the average porosity of limestones (1.4%). Their poro-perm relationships are similar, with the notable exception of planar-e type B dolomites, which generally display higher permeability values. The intensity of top bounded fractures is distinctly lower in coarse-crystalline dolomites than in fine-crystalline dolomites and limestones, both at the macro- and the micro-scale. On the other hand neither lithology (i.e. limestone vs. dolomite) nor dolomite crystal size control the intensity of perfect bed-bounded fractures, which is strictly controlled by the fracture layer thickness. Our results provide information that could be used as guidance for the characterization and modelling of fractured carbonate reservoirs made of interlayered limestones and dolomites. Highlights: Outcropping Albian interlayered dolomites and limestones analog of Basilicata reservoirs. Two types of early dolomites (fine-medium and coarse crystalline). All dolomites have matrix porosity and permeability higher then limestones. Top-bounded fracture intensity lower in coarse dolomites. Perfect bed-bounded fracture density controlled by layer thickness in all lithologies.